Penguatan Kemampuan Berpikir Matematis Mahasiswa pada Geometri Bidang dan Ruang - Tupulu, Nasri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This research is descriptive research, namely research that aims to describe students' mathematical thinking skills in plane and space geometry. The approach used is a case study. This research is a case study research because the focus of this research is on how to strengthen mathematical thinking skills. Development is constructed through theoretical reviews, synthesis of previous research, and examples of strengthening mathematical thinking skills. The sample in this study was 20 students. The results of interviews with students on plane and space geometry were obtained from the description of mathematical thinking skills apart from understanding the problem. The flow of this strengthening research was carried out for 5 essay questions to measure mathematical thinking skills and also validated to see the questions according to the indicators of mathematical thinking ability: 1) deepening, 2) guessing, 3) generalizing, and 4) convincing. The results of the study show that mathematical thinking skills have developed, can be seen from the fulfillment of indicators of mathematical thinking skills, namely: 1) students' deepening has been able to explore the geometry of planes and spaces in the subject of line alignment, 2) students can guess the criteria of the question and relate it to the previous material, 3) students can generalize questions with good reasoning, and 4) students can convince answers based on theorems and proofs. The results of interviews with students showed that the ability to think mathematically in the material of parallel lines and congruent angles was achieved.